METAPHOR OF COLORS IN INDONESIAN - I Dewa Putu Wijana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
This brief article deals with the use of Indonesian words referring to colors for creating metaphorical expressions. All data presented are collected from various sources, such as Kamus Besar Bahasa Indonesia (Indonesian Standard Dictionary), and added with data obtained from Oxford Advanced Leaner’s Dictionary, Indonesian proverb book, encyclopedia, terminology collection book, poetry anthology, song lyrics, and data of the author’s own creation as an Indonesian native speaker. Set aside from their literal meanings, the metaphorically used color words are collected and classified into two categories, i.e. achromatic and chromatic colors. Then, their universalities are determined by comparing them with English color metaphors. Finally the existence of specific Indonesian color metaphors are identified by correlating them with extra linguistic factors, such as environment, history, religion, politic and other socio cultural activities. A careful analysis on the data shows that there is nearly no significant difference in metaphorical uses of achromatic colors in English and Indonesian. However, despite universal nuances of chromatic color metaphors, some specific ones emerge due to various external factors, such as environment, education, history, politic, law, religion, literature, and other socio cultural facts that are specifically found and practiced in Indonesia.